Survival of Vibrio cholerae O1 and Vibrio parahaemolyticus in fried and boiled Malaysian fish sausage - Tang, John Yew Huat; Mohd Noor, Nurul Hidayah; Mazlan, Nurhidayah; Yeo, Chew Chieng; Abu Bakar, Che Abdullah; Radu, Son (Elsevier, 2014)
Survivability of Vibrio cholerae O1 and Vibrio parahaemolyticus in a popular Malaysian fish sausage snack, keropok lekor (either boiled or fried) in two conditions (closed or opened) was investigated by spiking ca. 8.00 log CFU/ml of each bacterial culture. Spread plate method onto TCBS agar was used to determine the numbers of inoculated vibrios that had survived as per tested condition. V. parahaemolyticus was more sensitive than V. cholerae O1 and lost viability in saline (control, closed condition). Both vibrios were not detected in the opened condition control after 1 h but keropok lekor proved to significantly support the viability of vibrios for up to 6 h. No significant growth or reduction (p > 0.05) was detected in an enclosed container but a significant reduction (p < 0.05) was observed in the opened condition over a 6 h incubation period. After 6 h incubation, V. cholerae survived at 7.95 ± 0.05 log CFU/g (boiled, enclosed), 6.11 ± 0.18 log CFU/g (fried, enclosed), 4.23 ± 0.48 log CFU/g (boiled, opened) and 3.08 ± 0.46 log CFU/g (fried, opened), respectively. Though V. parahaemolyticus showed poor viability in saline, they persisted well in keropok lekor with numbers recorded at 5.75 ± 0.09 log CFU/g (boiled, enclosed), 5.49 ± 0.59 log CFU/g (fried, enclosed), 2.85 ± 0.45 log CFU/g (boiled, opened) and 2.13 ± 0.52 log CFU/g (fried, opened), respectively. While vibrios are known to be easily killed by heat, post-cooking contamination might lead to food poisoning as a result from vibrios persistence in keropok lekor.